1991
DOI: 10.1007/bf01643231
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal transmission of chlamydia trachomatis. The use of serological tests in detecting infected women

Abstract: A study is presented on the use of serological tests for the detection of Chlamydia trachomatis in 273 pregnant women. 166 were cultured for C. trachomatis and nine (5.4%) were positive. Three culture-positive babies, all born to culture-positive women, had conjunctivitis. Elevated IgG and IgA antibody levels were seen in six (67%) and three (33%) of the infected women, respectively. Three (2.4%) of IgG antibody-negative mothers (n = 126) were positive by culture. Compared to serology culture of the microorgan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…In any case, our estimates for the timing of the mother's acquisition of the chlamydial infection, based on antitrachomatis antibodies obtained during the index pregnancy, show that a significant number of maternal C. trachomatis infections leading to an infected infant are acquired after the first trimester and would remain undiagnosed if screening were organised only during the first trimester. The sensitivity of C. trachomatis antibodies for recent infection is 67%–95%, that is, a lack of antitrachomatis antibody development during chlamydial infection has been demonstrated in 5%–33% of cases 5 14. We therefore consider that the lack of antibodies in a third of our mothers in the first trimester suggests that at least one quarter of the maternal genital chlamydial infections have occurred later in the pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…In any case, our estimates for the timing of the mother's acquisition of the chlamydial infection, based on antitrachomatis antibodies obtained during the index pregnancy, show that a significant number of maternal C. trachomatis infections leading to an infected infant are acquired after the first trimester and would remain undiagnosed if screening were organised only during the first trimester. The sensitivity of C. trachomatis antibodies for recent infection is 67%–95%, that is, a lack of antitrachomatis antibody development during chlamydial infection has been demonstrated in 5%–33% of cases 5 14. We therefore consider that the lack of antibodies in a third of our mothers in the first trimester suggests that at least one quarter of the maternal genital chlamydial infections have occurred later in the pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…We used data from those studies that reported both the number of infants exposed to C trachomatis and the number who developed confirmed C trachomatis conjunctivitis or pneumonia. [11][12][13][14][15][16][17][18][19][20][21][22][23] (Other types of studies, such as those that began with a set of infected infants, were not included because they could not be used to establish the incidence of symptomatic C trachomatis infections among exposed infants.) The data were aggregated, weighting studies in proportion to their sample size, to produce pooled estimates of probability.…”
Section: Incidence Of Conjunctivitis and Pneumoniamentioning
confidence: 99%
“…Studies that did not attempt to identify infants with pneumonia were used only for the probability estimate for conjunctivitis. 12,18 Those that were designed to study conjunctivitis but also reported the number of infants with pneumonia were included in the pneumonia calculation 22 unless the minimum follow-up was 1 month or less 21 (before the peak incidence of C trachomatis pneumonia at 6 to 9 weeks of age). 11 We did not include studies of maternal-infant transmission that documented microbiologic or serologic evidence of infection but did not report rates of conjunctivitis or pneumonia.…”
Section: Incidence Of Conjunctivitis and Pneumoniamentioning
confidence: 99%